A Twitter Sentimen Analysis on Islamic Banking Using Drone Emprit Academic (DEA): Evidence from Indonesia - Nadia Nurul Izza; Mia Sari; Mughnii Kahila; Solahuddin Al-Ayubi (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT The research aimed to identify and collect issues discussed regarding Islamic banking from user activity, sentimen, and content on Twitter. This study used a qualitative approach by collecting data on 145,475 conversations from Twitter using the Twitter Crawling technique with the Drone Emprit Academy (DEA) engine from 28 July 2020 – 10 March 2023 in Indonesia. Text data mining is used with the help of the DEA system by analyzing sentimen, Social Network Analysis (SNA), and other Twitter data analysis. The results showed that the highest number of tweets related to Islamic banking came from the number of tweets which were dominated by millennials and millennials with positive sentimens of 66%, then negative sentimens of 28% and neutral sentimens of 5%. From these results, both positive, negative and neutral sentimens are a challenge for various stakeholders in the field, including academics, government and others, in a more massive manner to explain and provide a more solid and stronger understanding of Islamic finance, especially Islamic banking.Keywords: Islamic Banking; Sentimen Analysis; Twitter; Academic Emprit Drone ABSTRAKPenelitian bertujuan untuk mengindetifikasi dan mengumpulkan isu yang dibahas terkait perbankan syariah dari aktivitas pengguna, sentimen, dan konten di Twitter. Metode ini menggunakan pendekatan kualitatif dengan mengumpulkan data 145.475 percakapan dari Twitter menggunakan teknik Twitter Crawling dengan mesin Drone Emprit Academy (DEA) dari tanggal 28 Juli 2020 – 10 Maret 2023 di Indonesia. Text data mining digunakan dengan bantuan sistem DEA dengan menganalisis sentimen, Social Network Analysis (SNA), dan analisis data Twitter lainnya. Hasil penelitian menunjukkan jumlah tweet tertinggi terkait perbankan syariah berasal dari jumlah tweet yang didominasi oleh kaum millennials dan zillenial dengan sentimen positif sebesar 66%, kemudian sentimen negatif 28% dan sentimen netral sebesar 5%. Dari hasil tersebut, baik sentimen positif, negative, maupun netral menjadi tantangan bagi berbagai pemangku kepentingan di lapangan, termasuk akademisi, pemerintah, dan lainnya, secara lebih massif untuk menjelaskan dan memberikan pemahaman yang lebih kokoh dan kuat tentang keuangan syariah khususnya perbankan syariah. Kata Kunci: Perbankan Syariah, Analisis Sentimen, Twitter, Drone Emprit Akademik